2013
DOI: 10.1016/j.mod.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling nanotubes, an emerging intercellular communication route in development

Abstract: The development of multi-cellular organisms involves a comprehensive and tightly regulated cell-to-cell communication system to coordinate the activity and behavior of individual cells. Diverse signaling pathways ranging from receptor-mediated signal transduction to contact-dependent communication via gap junctions achieve these complex interactions. In this review, we will focus on a new type of intercellular connection, the tunneling nanotube (TNT), which has been observed in many cell types in vitro and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
179
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(182 citation statements)
references
References 37 publications
1
179
0
1
Order By: Relevance
“…Some of these structures formed distinct intercellular bridges between MHC class IIþ dendritic cells. Furthermore, a number of in vivo studies demonstrate TNT-like structures during developmental processes in embryogenic tissues of vertebrates and invertebrates [107].…”
Section: Tunnelling-nanotube Type Of Wiring Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these structures formed distinct intercellular bridges between MHC class IIþ dendritic cells. Furthermore, a number of in vivo studies demonstrate TNT-like structures during developmental processes in embryogenic tissues of vertebrates and invertebrates [107].…”
Section: Tunnelling-nanotube Type Of Wiring Transmissionmentioning
confidence: 99%
“…Developing hippocampal neurons were demonstrated to form transient nanotubes with distant astrocytes [107,111]. TNTs were found to mediate both transient calcium signals and depolarization from distant astrocytes to neurons within a limited maturation period.…”
Section: (C) Astrocyte -Neuron Crosstalk In Developmentmentioning
confidence: 99%
“…In support of this, several cell lines are reported to form TNTs express mutated or inactive p53. 2,3 Thus, substantial evidence suggests that p53 is not a master protein for TNT formation and further investigation is needed to dissect the molecular mechanisms underlying their formation.…”
Section: I) Statistical Analyses Revealed 12mentioning
confidence: 99%
“…The recent discovery that TNT-like structures exist in vivo suggests they may have an important role during tissue development and maintenance. 2,3 TNTs facilitate intercellular transfer of various cellular components and are thought to represent a novel form of cellular communication. [1][2][3] Recently, it was reported that TNT formation in primary rat hippocampal astrocytes and neurons was dependent on the activation of tumor suppressor protein p53 through cellular stress induction such as hydrogen peroxide (H 2 O 2 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation